A Case of Spontaneous Pneumothorax with Persistent Air Leakage During the Course of COVID-19 - Saliha Kanık Yüksek; Aslinur Ozkaya Parlakay; Doğuş Güney; Belgin Gülhan; Gulsum Iclal Bayhan; Emrah Şenel (Galenos Publishing House, 2021)
Development of pneumothorax during the course of COVID-19 is very rare, and may occur secondary to severe pulmonary involvement causing alveolar damage in the parenchyma, or is seen as a complication of respiratory support. Until now, quite a few cases have been reported. Herein, we shared a case of spontaneous pneumothorax with persistent air leakage without any parenchymal or pleural involvement.